Nexilin Is Necessary for Maintaining the Transverse-Axial Tubular System in Adult Cardiomyocytes. (July 2020) - Spinozzi, Simone; Liu, Canzhao; Chen, Ze'e; Feng, Wei; Zhang, Lunfeng; Ouyang, Kunfu; Evans, Sylvia M.; Chen, Ju
Abstract : Background: NEXN (nexilin) is a protein of the junctional membrane complex required for development of cardiac T-tubules. Global and cardiomyocyte-specific loss of Nexn in mice leads to a rapidly progressive dilated cardiomyopathy and premature death. Therefore, little is known as to the role of NEXN in adult cardiomyocytes. Transverse-axial tubular system remodeling are well-known features in heart failure. Although NEXN is required during development for T-tubule formation, its role, if any, in mature T-tubules remains to be addressed. Methods: Nexn inducible adult cardiomyocyte-specific KO mice were generated. Comprehensive morphological and functional analyses were performed. Heart samples (n>3) were analyzed by molecular, biochemical, and electron microscopy analyses. Isolated single adult cardiomyocytes were analyzed by confocal microscopy, and myocyte shortening/re-lengthening and Ca 2+ transient studies were conducted. Results: Inducible cardiomyocyte-specific loss of Nexn in adult mice resulted in a dilated cardiomyopathy with reduced cardiac function (13% reduction in percentage fractional shortening; P <0.05). In vivo and in vitro analyses of adult mouse heart samples revealed that NEXN was essential for optimal contraction and calcium handling and was required for maintenance of T-tubule network organization (transverse tubular component in Nexn inducible adult cardiomyocyte-specific KO mice reduced by 40% with respect to controls, P <0.05). Conclusions: Results here reported reveal NEXN to be a pivotal component of adult junctional membrane complexes required for maintenance of transverse-axial tubular architecture. These results demonstrate that NEXN plays an essential role in the adult cardiomyocyte and give further understanding of pathological mechanisms responsible for cardiomyopathy in patients carrying mutations in the NEXN gene. Abstract : Supplemental Digital Content is available in the text.